Earnings Management Under Pressure: The Effects of Environmental Uncertainty, Financial Distress, and CSR Disclosure - Tria Susanti; Sumaryanto Sumaryanto (Universitas Muhammadiyah Semarang, 2026)
Earnings are often a primary concern for stakeholders, which may encourage management to engage in earnings management practices, particularly when firms face internal and external pressures. This study aims to investigate the effect of environmental uncertainty, financial distress, and CSR disclosure on earnings management practices. The population consists of manufacturing companies listed on the Indonesia Stock Exchange for the 2021–2024 period. The sample was selected through purposive sampling, yielding 344 observations, which were analyzed using panel data regression. The results indicate that environmental uncertainty does not affect earnings management practices. However, financial distress and CSR disclosure negatively affect earnings management. This study simultaneously examines the three factors to analyze earnings management practices during the observation period using appropriate measurement approaches. This study adds to the empirical evidence on the determinants of earnings management by highlighting the role of internal factors, particularly financial distress and CSR disclosure. These findings provide practical implications for investors, creditors, and regulators by emphasizing the importance of evaluating firms' financial conditions and the quality of CSR disclosure to identify potential earnings management and improve the quality of economic decision-making.